Sodium-ion battery negative electrode material, negative electrode plate, preparation method of negative electrode plate, sodium-ion battery and electric device
By combining hard carbon and soft carbon in a reasonable ratio and performing nano-processing, the conductivity and order of the sodium-ion battery anode material are improved, the sodium deposition problem is solved, high specific capacity and cycle stability are achieved, and the charge and discharge performance of sodium-ion batteries is optimized.
Patent Information
- Application Number
- CN202411183876.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-01-10
AI Technical Summary
Existing sodium-ion batteries are prone to sodium deposition at the interface of the hard carbon negative electrode when charged at high rates, which affects battery capacity and limits their use at high rates.
Hard carbon and soft carbon were combined in a mass ratio of (5-8):(2-5) as the negative electrode material. The D50 particle size of the nano-hard carbon was ≤1μm. The negative electrode sheet was prepared by combining it with conductive agent and binder to improve the order and conductivity of the negative electrode and suppress sodium precipitation.
While ensuring high specific capacity, it effectively suppresses sodium deposition, improves the overall electrochemical performance and cycle stability of the anode material, and takes into account rate performance.
Smart Images

Figure CN119297277A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sodium ion batteries, and in particular to a sodium ion battery negative electrode material, a negative electrode sheet and a preparation method thereof, a sodium ion battery and an electrical device. Background Art
[0002] Compared with lithium-ion batteries, sodium-ion batteries do not contain rare metal lithium, so they have the advantages of low cost and cheap and readily available raw materials. In order to meet the market demand for large-scale energy storage, sodium-ion batteries need to demonstrate excellent safety performance, cost-effectiveness and durability. The key to achieving these characteristics lies in the selection and optimization of battery materials. Further research and development of these materials is of great significance to promoting the transformation of sodium-ion battery technology to the market. In particular, the development of suitable negative electrode materials plays a vital role in promoting the development of sodium-ion batteries.
[0003] At present, when sodium-ion batteries are charged with a high-rate current, sodium precipitation is more likely to occur at the interface of the commonly used hard carbon negative electrode sheet, which seriously affects the capacity of the sodium-ion battery and limits the use of sodium-ion batteries at high rates.
[0004] Therefore, it is necessary to develop a negative electrode material for sodium-ion batteries that can achieve both rate performance and solve the sodium precipitation problem. Summary of the invention
[0005] The purpose of the present invention is to provide a sodium ion battery negative electrode material to address the deficiencies of the prior art, which can solve the sodium precipitation problem while taking into account the rate performance.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A sodium ion battery negative electrode material comprises a first negative electrode material and a second negative electrode material; wherein the mass ratio of the first negative electrode material to the second negative electrode material is (5-8):(2-5), the first negative electrode material is hard carbon, and the second negative electrode material is soft carbon.
[0008] Among them, the disordered structure of hard carbon leads to its low conductivity, and the sodium insertion potential of 0.1V (vs.Na+ / Na) in the low potential platform area of hard carbon is close to the sodium precipitation potential. Therefore, sodium precipitation is prone to occur on the surface of hard carbon negative electrode at high current density. Compared with hard carbon, the arrangement of graphite microcrystals inside soft carbon is relatively orderly, and the width and thickness of the microcrystal layer are larger; in addition, the capacity contribution of soft carbon negative electrode mainly comes from the slope area.
[0009] Therefore, nano-hard carbon and soft carbon are used as negative electrodes in the ratio of (5-8): (2-5), so that when sodium ions are embedded in the negative electrode, the order of the negative electrode is improved, thereby improving the conductivity of the negative electrode. Therefore, under the premise of improving the compaction of the negative electrode and ensuring the capacity, the problem of easy sodium precipitation in the negative electrode is solved. When the proportion of soft carbon is less than 2, the high proportion of hard carbon will easily cause sodium precipitation at high current density; when the proportion of soft carbon is greater than 5 parts, the specific capacity of the soft carbon itself is low, resulting in low specific capacity of the mixed negative electrode.
[0010] Preferably, the first negative electrode material is nano-hard carbon, and the D50 particle size of the nano-hard carbon is ≤1 μm. When it is larger than a preset range, the negative electrode will have poor rate performance at high current density due to a longer sodium ion diffusion path.
[0011] Preferably, the peak intensity ratio ID / IG between the D peak and the G peak of the negative electrode material in the Raman spectrum is 1.02-1.08.
[0012] In addition, the present invention also provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material coating coated on at least one surface of the negative electrode current collector, wherein the negative electrode active material coating comprises the above-mentioned sodium ion battery negative electrode material.
[0013] In addition, the present invention also provides a method for preparing a negative electrode sheet for a sodium ion battery, comprising the following steps:
[0014] S1, carbonizing a soft carbon precursor to obtain soft carbon;
[0015] S2, mixing nano-sized hard carbon, soft carbon, conductive agent, binder and water, adjusting the solid content to 1-5%, to obtain negative electrode slurry;
[0016] S3, coating the negative electrode slurry on at least one surface of the negative electrode current collector, drying, rolling and die-cutting to obtain the negative electrode sheet of the sodium ion battery.
[0017] Preferably, in step S1, the carbonization temperature is 1200-1500°C.
[0018] Preferably, the conductive agent includes one or more combinations of acetylene black, superconducting carbon black, graphite emulsion, carbon nanotubes, graphene, Ketjen black and vapor-grown carbon fibers.
[0019] Preferably, the binder includes one or more combinations of polyvinylidene fluoride, sodium alginate, polyvinyl alcohol, polymethyl methacrylate, hydrogenated nitrile rubber, polytetrafluoroethylene, polyacrylic acid, carboxymethyl cellulose and styrene-butadiene rubber emulsion.
[0020] In addition, the present invention also provides a sodium ion battery, comprising a battery cell formed by winding a negative electrode sheet, a positive electrode sheet and a separator, an electrolyte, and a shell that encapsulates the battery cell and the electrolyte, wherein the negative electrode sheet is the above-mentioned negative electrode sheet.
[0021] In addition, the present invention also provides an electrical device, comprising the above-mentioned sodium ion battery.
[0022] Compared with the prior art, the beneficial effects of the present invention are:
[0023] 1) The present invention effectively improves the comprehensive electrochemical performance of the negative electrode material by compounding hard carbon and soft carbon in a reasonable proportion, taking into account both the rate performance and the sodium precipitation problem. Among them, hard carbon has a high specific capacity and good cycle stability, but its disordered structure leads to low conductivity, and the sodium insertion potential in the low potential platform area is close to the sodium precipitation potential. Sodium precipitation is prone to occur under high current density, affecting the safety and cycle life of the battery. Although the specific capacity of soft carbon is relatively low, its internal graphite crystallites are arranged in an orderly manner, the width and thickness of the microcrystalline layer are larger, the conductivity is higher, and the capacity contribution mainly comes from the slope area, avoiding the risk of sodium precipitation in the low potential platform area. Compounding the two carbon materials in a reasonable proportion can give play to their respective advantages. Hard carbon provides high specific capacity, and soft carbon improves the comprehensive conductivity of the material and inhibits sodium precipitation, thereby obtaining a composite negative electrode material that takes into account both rate performance and cycle stability.
[0024] 2) The present invention controls the mass ratio of hard carbon to soft carbon to be (5-8): (2-5), while ensuring a high specific capacity, the comprehensive conductivity of the negative electrode material and the effect of inhibiting sodium precipitation are maximized. Among them, hard carbon is the main capacity source of the composite negative electrode material, and its content directly determines the specific capacity of the negative electrode. However, if the hard carbon content is too high, the problem of sodium precipitation will become prominent, the conductivity will decrease, and the rate performance will deteriorate. Although the capacity of soft carbon is relatively low, its conductivity is high and it can effectively inhibit sodium precipitation. Therefore, it is necessary to increase the content of soft carbon as much as possible while ensuring a high specific capacity to obtain the best comprehensive electrochemical performance. The present invention finds that when the mass ratio of hard carbon to soft carbon is in the range of (5-8): (2-5), the comprehensive performance of the composite negative electrode material is optimal. At this ratio, hard carbon provides a sufficiently high specific capacity, while the addition of soft carbon effectively improves the conductivity of the material and inhibits the problem of sodium precipitation, so that the composite negative electrode material can still maintain excellent charge and discharge performance and cycle stability at high current density. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic diagram of the electrode surface of the sodium ion battery of Example 1 of the present invention after cycling.
[0026] Figure 2 This is a schematic diagram of the electrode surface of the sodium ion battery of Example 2 of the present invention after cycling.
[0027] Figure 3 This is a schematic diagram of the electrode surface of the sodium ion battery of Comparative Example 1 of the present invention after cycling. DETAILED DESCRIPTION
[0028] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] According to the first aspect of the present application, the present application provides a sodium ion battery negative electrode material, which includes a first negative electrode material and a second negative electrode material; wherein the mass ratio of the first negative electrode material to the second negative electrode material is (5-8): (2-5), the first negative electrode material is hard carbon, and the second negative electrode material is soft carbon.
[0030] In some embodiments, the mass ratio of the first negative electrode material to the second negative electrode material is (5-8):
[0031] (2-5), for example, it can be 5:5, 6:4, 7:3, 8:2.
[0032] In some embodiments, the first negative electrode material is nano-sized hard carbon, and the D50 particle size of the nano-sized hard carbon is ≤1 μm.
[0033] In some embodiments, the peak intensity ratio ID / IG of the D peak and the G peak in the Raman spectrum of the negative electrode material is 1.02-1.08.
[0034] According to the second aspect of the present application, the present application provides a sodium ion battery negative electrode sheet, comprising a negative electrode collector and a negative electrode active material coating coated on at least one surface of the negative electrode collector, wherein the negative electrode active material coating comprises the above-mentioned sodium ion battery negative electrode material.
[0035] According to a third aspect of the present application, the present application provides a method for preparing a negative electrode sheet for a sodium ion battery, comprising the following steps:
[0036] S1, carbonizing a soft carbon precursor to obtain soft carbon;
[0037] S2, mixing nano-sized hard carbon, soft carbon, conductive agent, binder and water, adjusting the solid content to 1-5%, to obtain negative electrode slurry;
[0038] S3, coating the negative electrode slurry on at least one surface of the negative electrode current collector, drying, rolling and die-cutting to obtain the negative electrode sheet of the sodium ion battery.
[0039] In some embodiments, in step S1 , the carbonization temperature is 1200-1500° C. For example, it may be 1200° C., 1250° C., 1300° C., 1350° C., 1400° C., 1450° C., or 1500° C.
[0040] In some embodiments, the conductive agent includes a combination of one or more of acetylene black, superconducting carbon black, graphite emulsion, carbon nanotubes, graphene, Ketjen black, and vapor-grown carbon fibers.
[0041] In some embodiments, the binder includes a combination of one or more of polyvinylidene fluoride, sodium alginate, polyvinyl alcohol, polymethyl methacrylate, hydrogenated nitrile rubber, polytetrafluoroethylene, polyacrylic acid, carboxymethyl cellulose, and styrene-butadiene rubber emulsion.
[0042] According to a fourth aspect of the present application, the present application provides a sodium ion battery, comprising a battery cell wound with a negative electrode sheet, a positive electrode sheet and a separator, an electrolyte, and a shell encapsulating the battery cell and the electrolyte, wherein the negative electrode sheet is the above-mentioned negative electrode sheet. The separator can be selected from various separators used in sodium ion batteries known to those skilled in the art, such as polypropylene microporous membrane, polyethylene felt, glass fiber felt or ultrafine glass fiber paper.
[0043] The sodium ion battery provided by the present invention also includes an electrolyte, which is composed of an organic solvent and an electrolyte sodium salt. The organic solvent can be selected from one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, methyl acetate, ethyl propionate, fluoroethylene carbonate, ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and methyl tert-butyl ether; the electrolyte sodium salt can be selected from one or more of sodium hexafluorophosphate, sodium bis(trifluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, sodium difluorophosphate and sodium perchlorate.
[0044] According to a fifth aspect of the present application, the present application provides an electrical device comprising the above-mentioned sodium ion battery.
[0045] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.
[0046] Example 1
[0047] (1) Preparation of positive electrode
[0048] 9.2g of sodium nickel iron manganese oxide positive electrode material and 0.5g of conductive agent (SP) were dispersed into 12g of 4% PVDF glue.
[0049] The slurry is prepared by high-speed dispersion and uniform mixing; the positive electrode slurry is coated on the positive electrode current collector and dried, rolled and die-cut to obtain the positive electrode sheet of the sodium ion battery. (2) Preparation of negative electrode sheet
[0050] S1, carbonizing the soft carbon precursor needle coke at 1500°C to obtain soft carbon;
[0051] S2, dispersing 4.75 g of nano-hard carbon and 4.75 g of soft carbon into 10 g of carboxymethyl cellulose (CMC) glue with a solid content of 2%, and then adding 0.1 g of conductive agent (SP) and 0.2 g of styrene-butadiene rubber latex (SBR) to obtain a negative electrode slurry;
[0052] S3, coating the negative electrode slurry on the negative electrode current collector and drying, rolling, and die-cutting to obtain the negative electrode sheet of the sodium ion battery.
[0053] (3) Preparation of diaphragm
[0054] Polyethylene (PE) polymer film is used as the isolation membrane.
[0055] (4) Preparation of electrolyte
[0056] An organic solution is obtained by uniformly mixing the following components and mass ratios: ethylene carbonate (EC): propyl propionate (PP): vinylene carbonate (VC): diethyl carbonate (DEC): propylene carbonate (PC) = 22:25:3:28:22; sodium hexafluorophosphate is added to the organic solution, and the mass ratio of the added mass to the organic solution is 9.5:90.5; and an electrolyte is obtained after uniform mixing.
[0057] (5) Preparation of batteries
[0058] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order and wound to obtain an electrode assembly; the electrode assembly is placed in a packaging shell, an electrolyte is injected into the packaging shell and the packaging is packaged to finally obtain a sodium ion battery.
[0059] Example 2
[0060] Different from Example 1, the preparation of the negative electrode sheet in this example is as follows:
[0061] S1, carbonizing the soft carbon precursor needle coke at 1500°C to obtain soft carbon;
[0062] S2, dispersing 7.6 g of nano-hard carbon and 1.9 g of soft carbon into 10 g of carboxymethyl cellulose (CMC) glue with a solid content of 2%, and then adding 0.1 g of conductive agent (SP) and 0.2 g of styrene-butadiene rubber latex (SBR) to obtain a negative electrode slurry;
[0063] S3, coating the negative electrode slurry on the negative electrode current collector and drying, rolling, and die-cutting to obtain the negative electrode sheet of the sodium ion battery.
[0064] The rest is the same as Example 1 and will not be described again here.
[0065] Example 3
[0066] Different from Example 1, the nano-sized hard carbon in this example is 6.65 g and the soft carbon is 2.85 g.
[0067] The rest is the same as Example 1 and will not be described again here.
[0068] Example 4
[0069] Different from Example 1, the nano-sized hard carbon in this example is 5.7 g and the soft carbon is 3.8 g.
[0070] The rest is the same as in Example 1 and will not be described again.
[0071] Different from Example 1, in the step S1 of preparing the negative electrode sheet in this embodiment, the carbonization temperature is 1200°C.
[0072] The rest is the same as Example 1 and will not be described again here.
[0073] Comparative Example 1
[0074] Different from Example 1, the negative electrode material in this comparative example only contains nano-sized hard carbon and no soft carbon.
[0075] The rest is the same as Example 1 and will not be described again here.
[0076] Comparative Example 2
[0077] The difference from Example 1 is that the negative electrode material in this comparative example contains only soft carbon and no nano-sized hard carbon. The rest is the same as Example 1 and will not be described again.
[0078] Comparative Example 3
[0079] Different from Example 1, in this comparative example, the amount of nano-sized hard carbon is 1.9 g and the amount of soft carbon is 7.6 g.
[0080] The rest is the same as that of Comparative Example 1 and will not be described again.
[0081] Comparative Example 4
[0082] Different from Example 1, in this comparative example, the amount of nano-sized hard carbon is 3.8 g, and the amount of soft carbon is 5.7 g.
[0083] The rest is the same as that of Comparative Example 1 and will not be described again.
[0084] Comparative Example 5
[0085] Different from Example 1, in this comparative example, the amount of nano-sized hard carbon is 2.85 g, and the amount of soft carbon is 6.65 g.
[0086] The rest is the same as that of Comparative Example 1 and will not be described in detail here.
[0087] The sodium ions prepared in the above examples and comparative examples were tested, and the obtained data are shown in Table 1 below.
[0088] (1) Sodium analysis test:
[0089] The battery cell was charged to 3.9V at 2C, left for 5 minutes, and discharged to 1.5V at 2C, and the cycle was repeated 50 times. The battery cell was then fully charged at 2C and disassembled for analysis.
[0090] (2) Capacity retention rate:
[0091] 1. Charge the battery cell to 3.9V with a current of 2C, leave it for 5 minutes, discharge it to 1.5V at 2C, and record the discharge capacity C0. Charge the battery cells of the implementation case and the comparative example to 3.9V with a current of 2C, leave it for 5 minutes, and discharge it to 1.5V at 2C for 100 cycles. The 100th discharge capacity is C1, that is, the capacity retention rate of 100 cycles of 2C is C1 / C0.
[0092] 2. Charge the battery cell with a current of 0.5C to 3.9V, leave it for 5 minutes, discharge it with a current of 0.5C to 1.5V, record the discharge capacity C0, charge the battery cell with a current of 2C to 3.9V, record the charge capacity C1, and the 2C rate performance C1 / C0.
[0093] Table 1
[0094]
[0095]
[0096] From the data of Examples 1-5 and Comparative Examples 1-5, it can be seen that when the hard carbon and soft carbon in the negative electrode material are within the preset range, the sodium ion battery does not precipitate sodium while also having rate performance. When the negative electrode material contains only hard carbon, the sodium ion battery precipitates sodium and the capacity retention rate is poor.
[0097] Among them, from the comparison between Examples 1-4 and Comparative Examples 3-5, it can be seen that when the mass ratio of hard carbon to soft carbon is less than the preset range, it will lead to a lower capacity retention rate of the battery cell; when the mass ratio of hard carbon to soft carbon is greater than the preset range, it will lead to poor rate performance.
[0098] Depend on Figures 1 to 3 It can be seen that in this embodiment 1 ( Figure 1 ) and Example 2 ( Figure 2) sodium ion battery after cycling does not produce sodium precipitation on the electrode surface, while the comparative example 1 ( Figure 3 )'s sodium ion battery has obvious sodium deposition on the electrode surface after cycling.
[0099] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A sodium ion battery negative electrode material, characterized in that: It includes a first negative electrode material and a second negative electrode material; wherein the mass ratio of the first negative electrode material to the second negative electrode material is (5-8):(2-5), the first negative electrode material is hard carbon, and the second negative electrode material is soft carbon.
2. The sodium ion battery negative electrode material according to claim 1, characterized in that The first negative electrode material is nano-sized hard carbon, and the D50 particle size of the nano-sized hard carbon is ≤1 μm.
3. The sodium ion battery negative electrode material according to claim 1, characterized in that The peak intensity ratio ID / IG of the D peak and the G peak of the negative electrode material in the Raman spectrum is 1.02-1.
08.
4. A sodium ion battery negative electrode sheet, characterized in that: The invention comprises a negative electrode current collector and a negative electrode active material coating coated on at least one surface of the negative electrode current collector, wherein the negative electrode active material coating comprises the negative electrode material for a sodium ion battery according to any one of claims 1 to 3.
5. A method for preparing a negative electrode sheet for a sodium ion battery according to claim 4, characterized in that: The following steps are involved: S1, carbonizing a soft carbon precursor to obtain soft carbon; S2, mixing nano-sized hard carbon, soft carbon, conductive agent, binder and water, adjusting the solid content to 1-5%, to obtain negative electrode slurry; S3, coating the negative electrode slurry on at least one surface of the negative electrode current collector, drying, rolling and die-cutting to obtain the negative electrode sheet of the sodium ion battery.
6. The method for preparing a negative electrode sheet for a sodium ion battery according to claim 5, characterized in that: In step S1, the carbonization temperature is 1200-1500°C.
7. The method for preparing a negative electrode sheet for a sodium ion battery according to claim 5, characterized in that: The conductive agent includes one or more combinations of acetylene black, superconducting carbon black, graphite emulsion, carbon nanotubes, graphene, Ketjen black and vapor-grown carbon fibers.
8. The method for preparing a negative electrode sheet for a sodium ion battery according to claim 5, characterized in that: The binder includes one or more combinations of polyvinylidene fluoride, sodium alginate, polyvinyl alcohol, polymethyl methacrylate, hydrogenated nitrile rubber, polytetrafluoroethylene, polyacrylic acid, carboxymethyl cellulose and styrene-butadiene rubber emulsion.
9. A sodium ion battery, characterized in that: Including the sodium ion battery negative electrode sheet as described in claim 4.
10. An electrical device, characterized in that: Including the sodium ion battery as described in claim 9.